Digital Library Service Innovation in Higher Education: : A Comparative Study of IPDN and Universiti Kebangsaan Malaysia using Diffusion of Innovation and Bibliometric Analysis - Zahra Aqilah Dytihana; Mohammad Rezza Fahlevvi; Wenty Zahrati; Noordeyana Tambi (Indonesian Journal of Librarianship, 2026)
Background/Problem Statement: The rapid development of information technology has encouraged higher education institutions to innovate in library services, particularly through the implementation of digital libraries. However, gaps remain in service quality, levels of innovation adoption, and international collaboration among academic libraries, including those of the Institute of Home Affairs Governance (Institut Pemerintahan Dalam Negeri/IPDN) and Universiti Kebangsaan Malaysia (UKM). Purpose: This study aims to examine the comparative innovation of digital library services at IPDN and Universiti Kebangsaan Malaysia (UKM) using a Diffusion of Innovation perspective to improve the quality of information services and digital literacy in higher education. Method: This research employs a qualitative approach using documentation studies supported by bibliometric analysis. Data were collected from scholarly publications, institutional reports, and documents related to the development of digital libraries at IPDN and UKM. Data analysis was conducted using a descriptive-analytical method based on Everett Rogers’ diffusion of innovation theory to examine the adoption process, innovation characteristics, and patterns of acceptance of digital library services. Result: The findings indicate that, based on five main indicators—(1) service accessibility, (2) compatibility with academic needs, (3) system complexity, (4) user adoption level, and (5) innovation sustainability—digital library services at Universiti Kebangsaan Malaysia (UKM) demonstrate greater advantages compared to Institut Pemerintahan Dalam Negeri (IPDN). These advantages are particularly evident in broader information accessibility, higher compatibility with academic requirements, and a more significant level of innovation adoption among users. Meanwhile, IPDN shows progress in the initial implementation of innovation but still faces limitations in optimizing the utilization of digital services. In addition, the bibliometric analysis reveals a significant increase in scholarly publications related to digital libraries and digital literacy, indicating growing academic attention to these topics in a global context. Conclusion:  This study concludes that digital library services at Universiti Kebangsaan Malaysia (UKM) are superior to those at Institut Pemerintahan Dalam Negeri (IPDN) in terms of accessibility, compatibility, and user adoption, while IPDN continues to face challenges related to system complexity and innovation sustainability. These findings contribute theoretically to the Diffusion of Innovation literature and offer practical implications for the development of digital library services in higher education.